LANTUNAN EB SUKU YAGHAI MAPPI PAPUA: HUBUNGAN MAKNA, BENTUK, DAN STRUKTUR - Septina Rosalina Layan (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2021)
Eb is an oral tradition of singing that lives and develops in Yaghai tribe of Papua. Eb tells the story of human life in their relationship with other human beings, nature, and God. Eb tradition has been practiced and preserved up to now. The current study attempts to record, study, and analyse the form and structure of Eb and the relationship with its meaning. Sources of data are field observation notes, interviews, audio and video recordings, and photos, collected from participatory observation and interviews. The result of the study demonstrates that the chant forms of ordinary Eb and Oghob are without time signature, while the Qaqau Eb has a definite beat. Ordinary Eb is associated with universal joy, Qaqau Eb is associated with happy expression, while Oghob is associated with sorrow or sadness. The form and structure of Eb chant, such as the flow of melody, tempo, harmony, are closely related naturally to the meaning of the chant itself. Eb tradition has been inherited from generation to generation signifying cultural values of human ideas of the Yaghai Tribe